2007
DOI: 10.1038/sj.emboj.7601959
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-affinity LFA-1 binds α-actinin-1 to control migration at the leading edge of the T cell

Abstract: T lymphocytes use LFA-1 to migrate into lymph nodes and inflammatory sites. To investigate the mechanisms regulating this migration, we utilize mAbs selective for conformational epitopes as probes for active LFA-1. Expression of the KIM127 epitope, but not the 24 epitope, defines the extended conformation of LFA-1, which has intermediate affinity for ligand ICAM-1. A key finding is that KIM127-positive LFA-1 forms new adhesions at the T lymphocyte leading edge. This LFA-1 links to the cytoskeleton through α-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 43 publications
5
148
0
Order By: Relevance
“…Our data suggest that the intermediate affinity state observed in the literature for the related β 2 integrin LFA-1 (16)(17)(18)(19)(20) does not have to come from an individual conformational state, but could instead result from a mixture of conformational states. Previous studies showed that LFA-1 binding to ICAM-3, compared with ICAM-1, required more activation as defined by the number of activation agents needed (19)(20)(21).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our data suggest that the intermediate affinity state observed in the literature for the related β 2 integrin LFA-1 (16)(17)(18)(19)(20) does not have to come from an individual conformational state, but could instead result from a mixture of conformational states. Previous studies showed that LFA-1 binding to ICAM-3, compared with ICAM-1, required more activation as defined by the number of activation agents needed (19)(20)(21).…”
Section: Discussionmentioning
confidence: 68%
“…MEM148 did not bind to bent α X β 2 , in agreement with studies that show the presence of the closed headpiece in the bent conformation of α X β 2 (4). m24 also is a reporter of β 2 integrin activation and is widely used to detect high affinity LFA-1 on intact cells (16,32,33). m24 binds to residues near the MIDAS and in the βI domain, including Arg-122 and Glu-175 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a and Fig. 3 f; Smith et al, 2005;Stanley et al, 2008), and thus, could represent regions of T cell adhesion to ICAM-1 on the apical plasma membrane of EC and on the basal membrane after TEM (Millán et al, 2006). FRET efficiency was not dependent on the probe concentration (Fig.…”
Section: Roles Of Rocks and The Rhogef Gef-h1 In The Uropodmentioning
confidence: 97%
“…Similar clusters of active LFA-1 have been observed in the lamellipodia of T cells migrating on a rigid substrate coated with ICAM-1. 40,41 It has been hypothesized that RhoA and ROCK are involved in switching LFA-1 from a high to low affinity for ICAM-1, thereby disengaging LFA-1 from ICAM-1 and allowing migration forwards. 41 Inhibition of Rho or ROCK promoted integrin clustering in T cells 42 supporting a role for RhoA in disassembly of integrin clusters.…”
Section: A Possible Role For Rhoa In Integrin Clustersmentioning
confidence: 99%